Case Report: A case of uterine leiomyosarcoma metastasized to the vena cava, excised with the aid of preoperative CT three-dimensional imaging - Long, Ling; Zhou, Ling; Ying, Demei; Huang, Yan; Yang, Juan; Zhou, Lu; Li, Sufen; He, Xuan; Xie, Rongkai (Frontiers in Oncology, 2022)
Leiomyosarcoma of the uterus (ULMS) is a rare malignant tumor originating from embryonic mesenchymal cells. ULMS tends to metastasize to the lungs, lymph nodes, liver, and bone. Computed tomography three-dimensional (CT 3D) imaging is an advanced diagnostic technique that can track the vessels and their relationships with tumors and reveal the invasion of vessels, including small vessels, around tumors in any slice. Here, we describe a case in which ULMS extended to the retrohepatic inferior vena cava. To date, no report has described resection of metastatic ULMS of the vena cava through supplemental CT 3D imaging. Our patient presented with right lumbar abdominal pain as the main symptom. After using CT 3D reconstruction to accurately assess the relationship between the tumor and the surrounding organs and blood vessels before the operation, the operation was successfully completed through multidisciplinary surgical collaboration.